Western Polissian Parentheses Aimed at Attracting Listener's Attention (Linguostylistic Studies, 2017)
In coherent speech certain verbs, having lost their lexical meaning, turn into parentheses with various semantic shades. The study has identified a group of lexemes aimed at attracting attention of the listener. The analysis of the parentheses is based on the case study of spontanous speech of Western Polissian residents from three areas: Volyn Polissia, Brest Region and Podliashcheie. It has been revealed that certain lexemes used to attract attention of the interlocutor, are common for both literary and dialectic language (бачите, вірите, знаєте, чуєте), while some of them are used only in dialects (such as визʹ|мʼіте, |в’едайете, |думайете, |дáǐми, по|вʼірте, понʹі|майете, прис|тав).
Keywords: parentheses; atracting attention of a listener; Ukrainian Western Polissian dialects